1980
DOI: 10.1007/bf00286676
|View full text |Cite
|
Sign up to set email alerts
|

General resistance to late blight of Solanum tuberosum plants regenerated from callus resistant to culture filtrates of Phytophthora infestans

Abstract: Resistance of potato leaflets to culture filtrates of Phytophthora infestans is correlated with lower growth of the congenial parasite but not with lower sporulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…These results suggest that the higher level of leaf-spot resistance was likely due to either utilizing germplasm with an initially higher level of leaf-spot resistance (Daub, 1986), or that use of the pathogen at the whole plant level is a better selective agent than a culture filtrate used at the cellular level . Culture filtrates have been used successfully as selective agents Behnke, 1979Behnke, , 1980Sacristan, 1982 ;Hartman et al ., 1984), however, if the filtrate contains a nonspecific toxin, it is likely that only a partial resistance will be achieved . If culture filtrates are used in selection studies, it is generally recommended to generate as many resistant lines as possible because some of the lines may have been selected for resistance to components other than the putative toxin (Daub, 1986) .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the higher level of leaf-spot resistance was likely due to either utilizing germplasm with an initially higher level of leaf-spot resistance (Daub, 1986), or that use of the pathogen at the whole plant level is a better selective agent than a culture filtrate used at the cellular level . Culture filtrates have been used successfully as selective agents Behnke, 1979Behnke, , 1980Sacristan, 1982 ;Hartman et al ., 1984), however, if the filtrate contains a nonspecific toxin, it is likely that only a partial resistance will be achieved . If culture filtrates are used in selection studies, it is generally recommended to generate as many resistant lines as possible because some of the lines may have been selected for resistance to components other than the putative toxin (Daub, 1986) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of haploids for in-vitro selection for tolerance to salinity was demonstrated in datura (Tyagi et ai., 1981). The possibility to select for resistance to fungal pathogens, such as Heiminthosporium in maize (Gegenbach et ai., 1977), Phoma lingam in Brassica napus (Sacristan, 1982), Phytophthora infestans in potato (Behnke, 1979(Behnke, , 1980, Heiminothosporium sacchari in sugarcane (Heinz et ai., 1977), to bacterial pathogen Pseudomonas syringae (Carlson, 1973), to herbicide, e.g. picloram (Chaleff, 1983), chlorosulfuron and sulfometuron methyl (Chaleff and Ray, 1984), paraquat (Miller and Hughes, 1980) in tobacco, and glyphosate in Petunia hybrida (Shah et ai., 1986) and for changed metabolism in tobacco (Muller, 1983) has also been reported.…”
Section: Traits Amenable To In-vitro Selectionmentioning
confidence: 97%
“…Agronomically useful somaclonal variation, such as yield, quality (Matern et al 1978, Thomas et al 1982, Bright et al 1983, tuber shape, maturity date, and morphology of stem, leaf, and flower (Thomas et al 1982, Bright et al 1983) have been reported. Somaclonal variation for resistance to disease includes common scab (Streptomyces scabies), potato virus Y, potato leafroll virus, early blight (Alternaria solani), potato late blight (Phytophthora infestans), Fusarium wilt (Fusarium oxysporum) and blackleg (Erwnia cartivora) (Matern et al 1978, Thomas et al 1982, Bright et al 1983, Secor and Shepard 1981, Thomson et al 1986, Behnke 1979, Behnke 1980, Shepard 1981, Wenzel and Uhrig 1981, Wenzel 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chromosome doubling may be an alternate way to use diploids as a source of PTM resistance to introgress resistant traits into tetraploid potato clones. Several attempts on in vitro chromosome doubling by the use of zeatin roboside or benzilamino purine (BAP) have been made in potato breeding to introduce desirable traits from diploid lines to tetraploid lines (Roest and Bokelmann 1976, 1980, Orrillo and Watanabe 1994.…”
Section: Introductionmentioning
confidence: 99%